Comments on the paper "Are altered states of consciousness detrimental, useful or helpful for the origins of symbolic cognition? A response to Hodgson and Lewis Williams", by T Froese, A Woodward and T Ikegami. (August 2014) - Helvenston, Patricia
The purpose of these comments is to correct some mischaracterizations of my work with Paul Bahn that Froese et al. make in their latest paper "Are altered states of consciousness detrimental, useful or helpful for the origins of symbolic cognition? A response to Hodgson and Lewis-Williams". Additionally I discuss neuropsychological errors occurring in that paper.